Effectiveness Of Polyethylene on Hypothermic Events in Low Birth Weight - Haryoso Haryoso (Journal of Applied Nursing and Health, 2021)
Background: Treatment of low-birth-weight babies so far has mostly used incubators and swaddled babies using cloth whenever possible using the kangaroo method. While the kangoro method can be done if the mother and baby are both stable. Another way that can be done is to use a polyethylene blanket. The purpose of this study was to determine the use of polyethylene on the incidence of hypothermia in LBW. Methods: This type of research is a quasi-experimental design with Pre-Posttest Only Control Design, a sample of 60 LBW infants was taken by means of Systematic Random Sampling. Data collection techniques using the method of observation. Statistical analysis using the General Linear Model with a significant level of : 0.05 Results: The results obtained in this study are based on the overall analysis obtained p-value 0.000 <0.05, it can be interpreted that giving blankets polyethylene to respondents is effective in increasing the temperature of infants and reducing the incidence of hypothermia. Furthermore, the results of research based on Partial Eta analysis can be seen that blankets made of polyethylene increase the body temperature of low-birth-weight babies by 91.1%, while the increase in the kangaroo method group with Partial Eta 0.861 by 86.1%. Conclusion: This means that the use of blankets made from polyethylene increases the temperature higher than the kangaroo method.